The Information Literacy Level of Students at SMAN 1 Kubung and SMAN 1 Junjungsirih: A Comparative Study - Rahmi Fadhilah; Nurizzati Nurizzati (Darul Yasin Al Sys, 2026)
The growing importance of information literacy as a twenty-first-century competency has strengthened the need for students to identify information needs, search for relevant information, evaluate information credibility, and use information effectively and responsibly. However, information literacy skills among senior high school students remain varied, particularly across schools with different library management conditions. This study aims to analyze and compare the information literacy levels of eleventh-grade students at SMAN 1 Kubung and SMAN 1 Junjungsirih based on The Big6 framework. A quantitative approach with a descriptive-comparative research design was employed. The study population consisted of 401 students, from which 80 respondents were selected using proportionate stratified random sampling. Data were collected using a closed-ended questionnaire developed based on six indicators of The Big6 model: task definition, information-seeking strategies, location and access, use of information, synthesis, and evaluation. The validity test showed that all instrument items were valid, with correlation coefficients exceeding the r-table value of 0.361, while the reliability test produced a Cronbach’s Alpha coefficient of 0.971, indicating excellent reliability. The findings revealed that students’ overall information literacy level was categorized as high, with a grand mean score of 3.45. SMAN 1 Kubung obtained a higher average score of 3.58 than SMAN 1 Junjungsirih, which obtained a score of 3.36. The highest score was found in the task definition indicator, whereas the lowest score was identified in the synthesis indicator. The study concludes that differences exist in students’ information literacy levels between the two schools, influenced by learning environments, information resource management, and school library support systems. These findings contribute to the literature on school-based information literacy and provide practical implications for strengthening information literacy programs, optimizing the role of school librarians, and developing literacy-based learning strategies to enhance students’ critical and analytical thinking skills.